2013
DOI: 10.4338/aci-2012-12-ra-0055
|View full text |Cite
|
Sign up to set email alerts
|

Provider Use of and Attitudes Towards an Active Clinical Alert

Abstract: SummaryBackground: In a previous study, we reported on a successful clinical decision support (CDS) intervention designed to improve electronic problem list accuracy, but did not study variability of provider response to the intervention or provider attitudes towards it. The alert system accurately predicted missing problem list items based on health data captured in a patient's electronic medical record. Objective: To assess provider attitudes towards a rule-based CDS alert system as well as heterogeneity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…3843 A CDS system that uses an active interaction model, such as generating clinical alerts or reminders based on clinicians’ data entry and interaction, is the most effective in improving clinical practice. 39,44–46 In our study, the nurse preference to receive recommendations in the alert was refreshing, indicating they would adopt suggested interventions. In alert motivation, the finding that priorities of the patient, unit, and hospital were placed ahead of federal mandates and accreditation, which are most often more influential to physicians who may experience consequences of not meeting guidelines, was not surprising.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…3843 A CDS system that uses an active interaction model, such as generating clinical alerts or reminders based on clinicians’ data entry and interaction, is the most effective in improving clinical practice. 39,44–46 In our study, the nurse preference to receive recommendations in the alert was refreshing, indicating they would adopt suggested interventions. In alert motivation, the finding that priorities of the patient, unit, and hospital were placed ahead of federal mandates and accreditation, which are most often more influential to physicians who may experience consequences of not meeting guidelines, was not surprising.…”
Section: Discussionmentioning
confidence: 63%
“…40 However, fewer published studies 4143 have been assessments of attitudes and perception toward clinical alerts and CDS systems. Feblowitz et al 44 found that among health care providers, alert acceptance was 38.1% (interquartile ratio, 14.8%–54.4%), indicating the mass complexities of alerts. Studies on alarm fatigue indicated that most nurses (~95%) considered that false alarms reduced trust in alerts, disrupted clinical care, and desensitized members of the nursing staff.…”
Section: Discussionmentioning
confidence: 99%
“… • Users should be trained in using the problem list, its features and policies on the problem list. This increases the correct use of the problem list [ 12 , 14 , 25 , 40 , 42 ] • Experience in medicine and medical profession also influences the use of the problem list this should be taken into account in training of staff [ 17 , 25 , 41 ] • Training can increase the correct use of the problem list [ 12 , 14 , 25 , 40 , 42 ] Usability The definition of usability in this article is user-friendliness and user interface. • Custom views and filters should be possible [ 2 , 8 , 18 , 39 ] • The interface should be intuitive and efficient [ 8 , 13 , 39 ] • The encoded dictionary should be able to identify synonyms, misspelled entries and handle free text [ 2 , 6 , 12 , 31 , 32 ] • System support has to be integrated at logical moments in the notes registry (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Review of audit logs provides information on clinician behavior and on interactions between team members. 22,28 Previous studies have used audit logs to describe physician and care team behaviors including medical information queries, [29][30][31] team communication, 32 viewing of EHR notes, 23 response to *A total of 630 alerts were delivered to the InBaskets of PCPs who were logged into the EHR at the time of alert delivery or within 24 h of delivery; of these, 375 were opened within 24 h of delivery † Adjusted odds ratios account for clustering by PCP using a GEE model and control for PCP characteristics, patient characteristics and contextual factors clinical decision support tools, 33 and patient interactions through tethered portals. 34 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%